2020
DOI: 10.1177/1708538120913721
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between elevated serum uric acid and arterial stiffness in a healthy population

Abstract: Objective This study aims to investigate the relationship between serum uric acid and arterial stiffness in a healthy population. Methods Among the 979 participants, baPWV was non-invasively measured, the circulating levels of uric acid were tested, and the uric acid polymorphisms (rs2231142 and rs11722228) were genotyped. Then, the Mendelian randomization method was employed to test the relationship between serum uric acid and arterial stiffness in a healthy population. Results After adjusting for age, gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In addition, gout nephropathy, a form of chronic tubulointerstitial nephritis, induced by the deposition of urate precipitates in the distal collecting ducts and the medullary interstitium may cause progressive chronic kidney disease [4]. Furthermore, gout and hyperuricemia have been associated with a subset of comorbidities including metabolic syndrome, diabetes, hypertension as well as cardiovascular and cerebrovascular disease [5][6][7][8][9][10][11][12][13]. In most patients, the onset of gout occurs after the age of 60, with the incidence being about three times higher in men than in women [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, gout nephropathy, a form of chronic tubulointerstitial nephritis, induced by the deposition of urate precipitates in the distal collecting ducts and the medullary interstitium may cause progressive chronic kidney disease [4]. Furthermore, gout and hyperuricemia have been associated with a subset of comorbidities including metabolic syndrome, diabetes, hypertension as well as cardiovascular and cerebrovascular disease [5][6][7][8][9][10][11][12][13]. In most patients, the onset of gout occurs after the age of 60, with the incidence being about three times higher in men than in women [14].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies in the literature have investigated orthostatic BP changes with uric acid. In one study, Jiang et al found no relationship between serum uric acid levels and arterial stiffness causing OH development [16]. In another study, he found that association of high serum uric acid and increased arterial stiffness was dependent on cardiovascular risk factors in female population [17].…”
Section: Discussionmentioning
confidence: 99%
“…with claudication) or asymptomatic PAD would also have involvement of another arterial bed. 35 Polyvascular disease imposes the highest risk for new or recurrent cardiovascular events around the world. 68…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the polyvascular condition is more frequent in patients who present with PAD, than in those with CAD or CVD presentations. 35 PAD can, therefore, be considered a marker of disseminated atherosclerosis. These facts represent the main foundation of the INDAGA studies, a series of three multicenter registries designed to assess PAD in high-risk stable outpatients attending Internal Medicine, Cardiology, and Neurology clinics in Mexico.…”
Section: Introductionmentioning
confidence: 99%